Driver Safety Protocols, Emergency Response Systems, Insurance Coverage, and Customer Feedback on Service Quality in Indonesia's ride-hailing industry - Afifudin, Moch; Taufikur Rahman, Rahmat; Bahar, Anisa; Prananta, Arie Wahyu (IJBLE Scientific Publications Community Inc., 2024)
This study examines the impact of driver safety protocols, emergency response systems, insurance coverage, and customer feedback on service quality in Indonesia's ride-hailing industry. Utilizing a mixed-methods approach, quantitative data were collected from 400 ride-hailing users through a structured survey, while qualitative insights were gathered from 20 semi-structured interviews with drivers, customers, and company representatives. The findings indicate that emergency response systems have the most significant positive effect on service quality, followed by customer feedback and driver safety protocols. Although insurance coverage is also important, it demonstrated a comparatively lower impact. The study highlights the need for ride-hailing companies to enhance safety measures, improve communication regarding insurance, and develop robust customer feedback mechanisms to foster trust and satisfaction. These insights provide actionable recommendations for industry stakeholders and contribute to the theoretical understanding of service quality determinants in the ride-hailing context.